Routing table of DSDV in Mobile Ad-hoc Networking - Das, Smita (International Journal of Computer Sciences and Engineering, 2025)
In mobile ad-hoc networks a routing procedure is always needed to find a path so as to forward the packets appropriately between the source and the destination. A routing protocol is a protocol that specifies how routers communicate with each other. Each router has a knowledge only of networks attached to it directly. A routing protocol shares this information first among immediate neighbors, and then throughout the network. This way, routers gain knowledge of the topology of the network. An ad hoc routing protocol is a standard, that controls how nodes decide which way to route packets between computing devices in a network [10]. Various routing protocols available for Ad- hoc networks are AODV, CGSR, DSDV, DSR, OLSR, WRP, ZRP etc. In this paper DSDV is represented.